Estrogen Enhances FDFT1 Expression in Theca Cells of Chicken Hierarchical Ovarian Follicles by Increasing LSD1Ser54p Level Through GSK3β Phosphorylation at 216th Tyrosine - Yanhong Zhang; Conghao Zhong; Xinmei Shu; Qingxin Liu; Yunliang Jiang (Biomolecules)
The development of chicken ovarian follicles involves two key stages of primordial follicle recruitment and follicle selection that are tightly regulated by multiple reproductive hormones and cytokines. Our previous study revealed an estrogen-stimulated increase in the phosphorylation level of serine at position 54 of lysine demethylase 1A (LSD1Ser54p) in the theca cells of chicken hierarchical ovarian follicles (Post-TCs). In this study, we further found that the upregulation of LSD1Ser54p by estrogen was performed by glycogen synthase kinase 3 beta (GSK3β) and that GSK3β promoted LSD1Ser54p levels by directly binding to the SWIRM and AOL1 domains of LSD1. Upon estrogen stimulation, the phosphorylation level of tyrosine at position 216 of GSK3β (GSK3βTyr216p) increased, which enhanced the binding between LSD1 and GSK3β. The subsequent transcriptome sequencing on chicken Post-TCs treated with estrogen and CUT&RUN sequencing against the LSD1Ser54p protein revealed that the expression of the farnesyl-diphosphate farnesyltransferase 1 (FDFT1) gene was simultaneously upregulated by estrogen, GSK3β, and LSD1Ser54p. Moreover, the overexpression of FDFT1 further promoted cholesterol biosynthesis in chicken Post-TCs. In short, the findings of this study suggest that estrogen-induced tyrosine phosphorylation at position 216 of GSK3β can upregulate the level of LSD1Ser54p, leading to the activation of FDFT1 expression and subsequently promoting cholesterol biosynthesis in chicken Post-TCs, which may in turn enhance estrogen synthesis.